PENGUATAN HUKUM PENGADAAN BARANG DAN JASA PEMERINTAH UNTUK MEMPERCEPAT PEMBANGUNAN INDONESIA - Muhammad Rusydi (AL WASATH Jurnal Ilmu Hukum, 2020)
Indonesia's infrastructure development has become the government's top priority. This is continuous with the efforts of economic growth that has continued to be driven for five years. One year of change of government recorded, Indonesia's Economic Growth grew about 4.73% in September 2015. The development of infrastructure that continues to be driven must be supported by a strong legal standing to accelerate development. At present there is a new regulation regarding the law on procurement of government goods and services, namely Presidential Regulation Number 16 of 2018 concerning Procurement of Government Goods and Services, but seeing the urgency and needs in the field, the existence of Presidential Regulation number 16 of 2018 needs to be replaced with the type of regulation more than just a Presidential Regulation. The substitution could have been changed, which was originally a Presidential Regulation into a Law on the procurement of Government Goods and Services. Legal Strengthening the procurement of Government Goods and Services will be a strong foundation to accelerate development which is one of the priorities of the Indonesian government.